The Effect of Audio Visual Aids On The Level of Knowledge of Hemodialysis Patients - Yuanita Panma; Dhian Luluh Rohmawati; Rahmiwati (Risenologi, 2021)
Hemodialysis has a therapeutic effect on patients with chronic renal failure. However, on the other hand, it can also cause acute complications that can negatively affect the quality of life. Acute complications can be prevented by changing the lifestyle of hemodialysis patients, one of which is by using audio-visual aids. This study aims to determine the effect of audio-visual aids on the patient's level of knowledge about dealing with acute complications of hemodialysis. This study used a quasi-experimental design with pre and post-tests without a control group with 30 hemodialysis patients who met the inclusion criteria as respondents. This study indicates a significant effect between the use of audio-visual aids and the level of knowledge related to the management of acute complications in hemodialysis patients (p-value= 0,000). Therefore, nurses can use audio-visual aids as a means of education to deal with acute complications of hemodialysis.